Legal Protection for Parties Affected by Floods and Landslides in the Perspective of Civil Law - Novi Juli Rosani Zulkarnain (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2023)
This research aims to analyze the legal protection provided to individuals affected by floods and landslides from the perspective of civil law using a normative juridical method with a qualitative approach. Legal protection for those affected by natural disasters has become increasingly crucial considering the frequency and damage caused by floods and landslides in various regions. Through a qualitative approach, this study explores the civil law principles involving the responsibilities of landowners or users in relation to preventing hazards and damages. The analysis also encompasses the principle of legal responsibility in cases of negligence, where affected parties can seek accountability from others if it is proven that the losses occurred due to negligence. Furthermore, the research highlights the role of private agreements and property insurance as essential tools in protecting affected parties. Private agreements can help regulate obligations and responsibilities related to property damage or loss, while property insurance reduces the financial risk arising from property damage. Additionally, consumer protection is a focal point of the study, emphasizing protection against detrimental practices, such as the sale of disaster-prone properties without providing adequate information to buyers. The research also includes dispute resolution procedures in civil law as a means to resolve conflicts among affected parties. The findings of this research provide a deeper understanding of how civil law offers legal protection to those affected by floods and landslides and serve as a foundation for improvements and enhancements in the legal protection system when dealing with natural disasters.